2020
DOI: 10.3390/rs12091430
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Canopy Reflectance on the 3D Structure of Individual Trees in a Mediterranean Forest

Abstract: The characterization of 3D vegetation structures is an important topic, which has been addressed by recent research in remote sensing. The forest inventory requires the proper extraction of accurate structural and functional features of individual trees. This paper presents a novel methodology to study the impact of the canopy reflectance on the 3D tree structure. A heterogeneous natural environment in a Mediterranean forest, in which various tree species (pine, oak and eucalyptus) coexist, was covered using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…There are several methods for the automatic detection and parameters extraction on 3D models using crop height models [37], combining terrestrial laser scanner and UAV photogrammetric point clouds [38], fusing RGB and multispectral point clouds to extract individual tree parameters [39], computing 3D vegetation indices in olive groves [40], and obtaining forest structural attributes [41]. However, given the complexity and the unique characteristics of vineyard plots, such methods are not suitable to be applied.…”
Section: Individual Grapevine Detectionmentioning
confidence: 99%
“…There are several methods for the automatic detection and parameters extraction on 3D models using crop height models [37], combining terrestrial laser scanner and UAV photogrammetric point clouds [38], fusing RGB and multispectral point clouds to extract individual tree parameters [39], computing 3D vegetation indices in olive groves [40], and obtaining forest structural attributes [41]. However, given the complexity and the unique characteristics of vineyard plots, such methods are not suitable to be applied.…”
Section: Individual Grapevine Detectionmentioning
confidence: 99%
“…The estimation results showed that the relative RMSE of height ranged from 6.55% to 19.24%, and the errors depended on the architecture type and tree age. Jurado et al (2020b) assessed the impact of canopy reflectance based on the 3D tree structure of an individual treelevel forest inventory. Structural and spectral traits were extracted from images acquired using UAV-mounted RGB and multispectral cameras oriented at inclinations of 60° (for better 3D model reconstruction) and 90° (for accurate canopy reflectance measurement) relative to the ground.…”
Section: D Construction Using Triangulationmentioning
confidence: 99%
“…Tree height is a vital agronomic trait for assessing crop status and a vital selection parameter in breeding programs, especially in field conditions (Wiersma et al, 1986;Boukerrouand Rasmusson, 1990;Moles et al, 2009). Tree height estimation is also used as an indicator to estimate biomass (Persson and Fransson, 2017;Fernández-Sarría et al, 2019;Gennaro et al, 2020), yield (Sarron et al, 2018;López-Granados et al, 2019;Stateras and Kalivas, 2020), and health (Chang et al, 2020;Hobart et al, 2020;Jurado et al, 2020aJurado et al, , 2020b. In addition, canopy height from reconstructed 3D shape models is used to evaluate crop water status for irrigation planning.…”
Section: Tree Heightmentioning
confidence: 99%
“…The resulting 3D structures are modeled as a point cloud instead of a 3D mesh due to the fact that many complex geometric objects cannot be correctly triangulated. The SfM has been used for multiple purposes such as the vegetation reconstruction [19], cultural heritage [20], and archaeology [21]. Focusing on this last one, the 3D modeling of archaeological artifacts is usually carried out to study different characteristics using a virtual copy instead of the original.…”
Section: Point Cloud Reconstructionmentioning
confidence: 99%